Eksplorasi Limnologis Telaga Dringo, Banjarnegara, Jawa Tengah - Setefani Yulia Tiara Putri; Kharisma Dinda Islami; Laila Widi Utami; Suwarno Hadisusanto (Talenta Publisher, 2024)
Plankton are organisms that live floating in water bodies and move with the current. Plankton is a clue organism that can be used as a bioindicator because it is sensitive to environmental changes. The purpose of this study was to explore the limnological aspects of plankton distribution and diversity as bioindicators of water quality. In this study, 29 species of phytoplankton and 20 species of zooplankton were obtained, dominated by Nitzschia sp. and Asplanchna sp. The abundance index showed that the abundance of phytoplankton was 19386.67 ind/L and zooplankton was 5.33 ind/L. Water status based on phytoplankton diversity index with a value of 0.28-1.00 is categorized as low diversity and zooplankton diversity with a value of 0.78-1.97 is categorized as moderate diversity.